Madryt 1918. Sztuka i polska racja stanu - Piotr Rypson (Miejsce)
In Madrid of early 1918, a group of artists and writers, Józef Pankiewicz and Tadeusz Peiper among them, engaged in activities supporting Poland’s quest for independence. The article discusses the exhibition of Polish modern art they organised and subsequent events that led to the establishment of diplomatic mission and propaganda campaign on behalf of the Polish State.